Isolating membrane, preparation method thereof, and related secondary battery and electric device
By using nested structures of fibrous and fillers in the porous substrate surface coating of secondary batteries, the problem of taking into account both energy density and thermal safety performance is solved, and high cycling performance and dynamic performance is achieved. Improve, while reducing the risk of heat shrinkage and short circuit.
Patent Information
- Application Number
- CN202411272926.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-01-17
AI Technical Summary
When existing secondary batteries improve energy density and thermal safety performance, it is difficult to take into account high cycling performance and dynamic performance, and the insulation film lacks heat resistance and bonding strength, resulting in increased risk of heat shrinkage and positive and negative electrode short circuits.
The surface coating of porous substrate is adopted, and the coating is composed of fibrous materials and fillers. The fillers include a first filler and a second filler. The average particle size of the second filler is greater than the first filler. The heat resistance of the isolation film is improved through the nesting effect. and bond strength, and optimize the ionic conductivity and wetting characteristics of the coating through reasonable pore structure and filler ratio.
The high-thermal safety performance, good cycle performance and kinetic performance of the secondary battery are achieved, while reducing the risk of heat shrinkage and the probability of short-circuit of the positive and negative electrodes, and improving the heat resistance and ion conductivity of the isolation film.
Smart Images

Figure CN119324293A_ABST
Abstract
Description
[0001] This application is a divisional application based on the invention with application number 202280018074.0, application date December 5, 2022, applicant is Contemporary Amperex Technology Co., Ltd., and invention name is "Isolation membrane, preparation method thereof and related secondary batteries and electrical devices". Technical Field
[0002] The present application belongs to the field of battery technology, and specifically relates to an isolation membrane, a preparation method thereof, and related secondary batteries and electrical devices. Background Art
[0003] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the application and promotion of secondary batteries, their safety issues, especially thermal safety issues, have received more and more attention. However, the current methods for improving the thermal safety performance of secondary batteries are often not conducive to balancing the energy density and service life of secondary batteries. Therefore, how to make secondary batteries have both high energy density, high thermal safety performance, and good cycle performance and kinetic performance is the key challenge in the design of secondary batteries. Summary of the invention
[0004] The purpose of the present application is to provide an isolation membrane, a preparation method thereof, and related secondary batteries and electrical devices, which can enable the secondary battery to have high energy density, high thermal safety performance, and good cycle performance and kinetic performance.
[0005] In a first aspect, the present application provides an isolation membrane, comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein the coating comprises a fibrous material and a filler; the filler comprises a first filler and a second filler, and the average particle size of the second filler is greater than the average particle size of the first filler.
[0006] The coating includes fibrous materials and fillers, which helps to form a nesting effect between the filler and the fibrous materials, thereby increasing the heat resistance of the isolation membrane, reducing the degree of shrinkage of the isolation membrane when heated, reducing the risk of short circuit between the positive and negative electrodes, and making the secondary battery have high thermal safety performance, and maintaining high bonding strength between the coating and the porous substrate, preventing the filler from falling off during the long-term charging and discharging process of the secondary battery.
[0007] The average particle size of the second filler is larger than that of the first filler. The second filler has a larger particle size, so it can better play its supporting role in the coating, reduce the shrinkage of the first filler, and reduce the amount of binder, thereby improving the heat resistance of the isolation membrane; the second filler has a larger particle size, which helps to make the coating have more pore structures and less water content when the amount is small, thereby further improving the ion conductivity of the isolation membrane and the infiltration and retention characteristics of the electrolyte.
[0008] In any embodiment of the present application, the average particle size of the first filler is 15nm to 150nm, and can be optionally 15nm to 120nm. The first filler has the advantages of a small average particle size, a large specific surface area, and good affinity with fibrous materials, so that it can be better overlapped with the fibrous materials, so that the coating has a more stable spatial network structure, thereby increasing the ion conductivity of the isolation membrane, and improving the heat resistance of the isolation membrane and the infiltration and retention characteristics of the electrolyte. In addition, when the average particle size of the first filler is within the above range, the coating can also have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the isolation membrane.
[0009] In any embodiment of the present application, the first filler includes primary particles or secondary particles formed from primary particles.
[0010] In any embodiment of the present application, the average particle size of the primary particles is from 15 nm to 80 nm, and can be from 30 nm to 75 nm.
[0011] In any embodiment of the present application, the average particle size of the secondary particles is 50 nm to 150 nm, and can be 55 nm to 120 nm.
[0012] In any embodiment of the present application, the first filler includes inorganic particles, and the crystal form of the inorganic particles includes at least one of the θ crystal form, the γ crystal form and the η crystal form; optionally, the crystal form of the inorganic particles includes at least one of the θ crystal form and the γ crystal form.
[0013] In any embodiment of the present application, the content of the inorganic particles in the θ crystal form is ≥50 wt %, and may be 60 wt % to 82 wt %, based on the total weight of the inorganic particles in the first filler.
[0014] In any embodiment of the present application, the content of the γ-crystalline inorganic particles is ≥10 wt %, and can be optionally 17 wt % to 38 wt %, based on the total weight of the inorganic particles in the first filler.
[0015] In any embodiment of the present application, the content of the η-crystal inorganic particles is ≤5 wt %, and can be ≤1.5 wt %, based on the total weight of the inorganic particles in the first filler.
[0016] Selecting first fillers of different crystal types helps to improve at least one of the heat resistance, ion conductivity, and electrolyte wetting and retention properties of the separator.
[0017] In any embodiment of the present application, the BET specific surface area of the first filler is ≥15m 2 / g, optional 18m 2 / g to 65m 2 When the BET specific surface area of the first filler is within the above range, the coating can have a suitable average pore area, and the heat resistance and ion conductivity of the isolation membrane can be further improved; in addition, the affinity between the first filler and the fibrous material can be improved, so that the coating has a more stable spatial network structure, and the isolation membrane has better heat resistance and higher ion conductivity.
[0018] In any embodiment of the present application, the content of the first filler is ≥55wt%, and can be 60wt% to 90wt%, based on the total weight of the coating. When the content of the first filler is within the above range, the coating can have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the isolation membrane; in addition, it is also beneficial for the coating to have a more stable spatial network structure, thereby further improving the heat resistance and ion conductivity of the isolation membrane.
[0019] In any embodiment of the present application, the average particle size of the second filler is less than or equal to 400 nm, and can be optionally 100 nm to 300 nm.
[0020] In any embodiment of the present application, the second filler has a primary particle morphology.
[0021] In any embodiment of the present application, the BET specific surface area of the second filler is ≤15m 2 / g, optional 7m 2 / g to 12m 2 / g. When the BET specific surface area of the second filler is within the above range, the coating can have a suitable average pore area, and the heat resistance and ion conductivity of the separator can be further improved; in addition, the supporting role of the second filler can be better exerted, the moisture content of the coating can be reduced, and the coating can maintain a stable pore structure during long-term charge and discharge, which is beneficial to ion transmission and can also improve the heat resistance of the separator.
[0022] In any embodiment of the present application, the content of the second filler is ≤20wt%, and can be optionally 2wt% to 15wt%, based on the total weight of the coating. When the content of the second filler is within the above range, the coating can have a suitable average pore area, and the heat resistance and ion conductivity of the isolation membrane can be further improved; in addition, the supporting role of the second filler can be better exerted, the moisture content of the coating can be reduced, and the coating can maintain a stable pore structure during long-term charge and discharge, which is beneficial to ion transmission, and at the same time, the heat resistance of the isolation membrane can be improved.
[0023] In any embodiment of the present application, the second filler includes at least one of inorganic particles and organic particles.
[0024] In any embodiment of the present application, the second filler includes inorganic particles in the form of primary particles, and the crystal form of the inorganic particles in the form of primary particles includes at least one of α crystal form and γ crystal form, and optionally includes α crystal form. The second filler in the α crystal form has the advantages of high hardness, good heat resistance, low dielectric constant, high safety and high true density, thereby further improving the heat resistance of the coating.
[0025] In any embodiment of the present application, the second filler includes inorganic particles with a primary particle morphology, and the crystal form of the inorganic particles with a primary particle morphology includes an α-crystal form, and the content of the inorganic particles with an α-crystal form is ≥80wt%, optionally 90wt% to 100wt%, based on the total weight of the inorganic particles with a primary particle morphology in the second filler.
[0026] In any embodiment of the present application, along the thickness direction of the isolation membrane, the average pore area of the coating is smaller than the average pore area of the porous substrate;
[0027] The average pore area of the coating refers to the ratio of the total pore area of the coating in the cross-sectional image of the isolation membrane to the number of pores in the coating;
[0028] The average pore area of the porous substrate refers to the ratio of the total pore area of the porous substrate in the cross-sectional image of the separator to the number of pores in the porous substrate.
[0029] The average pore area of the coating is smaller than the average pore area of the porous substrate, so that the coating has high heat resistance; since the coating of the present application has high heat resistance, the thickness of the coating can be reduced (for example, the thickness of the coating can be less than or equal to 2 μm), shortening the active ion transmission distance, and thus the secondary battery can also take into account high energy density and good cycle performance and kinetic performance; in addition, since the coating of the present application has high heat resistance, a thinner porous substrate can be selected, thereby further improving the energy density of the secondary battery.
[0030] In any embodiment of the present application, along the thickness direction of the isolation membrane, the average pore area of the coating is recorded as S1, and the average pore area of the porous substrate is recorded as S2, then 0.06≤S1 / S2<1, optionally, 0.30≤S1 / S2≤0.97.
[0031] In any embodiment of the present application, 0.0002 μm 2 ≤S1≤0.0080μm 2 , optionally, 0.0004 μm 2 ≤S1≤0.0050μm 2 When the average pore area S1 of the coating is within the above range, the heat resistance of the separator can be improved on the one hand, and the active ion transmission will not be hindered on the other hand, thereby enabling the secondary battery to better balance high energy density, high thermal safety performance, and good cycle performance and kinetic performance.
[0032] In any embodiment of the present application, 0.0005 μm 2 ≤S2≤0.0100μm 2 , optionally, 0.0008 μm 2 ≤S2≤0.0080μm 2 When the average pore area S2 of the porous substrate is within the above range, it is beneficial to improve the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0033] In any embodiment of the present application, the average pore size of the isolation membrane is denoted as d1, and the average pore size of the porous substrate is denoted as d2, then d1 / d2<1; optionally, 0.3≤d1 / d2≤0.8. When the ratio d1 / d2 of the average pore size d1 of the isolation membrane to the average pore size d2 of the porous substrate is within the above range, the isolation membrane can have a high ion conductivity while ensuring high heat resistance.
[0034] In any embodiment of the present application, 15nm≤d1≤50nm, optionally, 20nm≤d1≤40nm. When the average pore size d1 of the isolation membrane is within the above range, on the one hand, the heat resistance of the isolation membrane can be improved, and on the other hand, the active ion transmission will not be hindered, thereby enabling the secondary battery to better balance high energy density, high thermal safety performance, and good cycle performance and kinetic performance.
[0035] In any embodiment of the present application, 25nm≤d2≤60nm, optionally, 30nm≤d2≤50nm. When the average pore size d2 of the porous substrate is within the above range, it is beneficial to improve the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0036] In any embodiment of the present application, the surface density of the coating is denoted as ρ1, and the surface density of the porous substrate is denoted as ρ2, then 0.15≤ρ1 / ρ2≤0.80; optionally, 0.20≤ρ1 / ρ2≤0.50. When ρ1 / ρ2 is within the above range, it is beneficial for the coating to have high heat resistance, and it is also beneficial for the secondary battery to have both high energy density and high thermal safety performance.
[0037] In any embodiment of the present application, optionally, 0.50 g / m 2 ≤ρ1≤1.50g / m 2 , more preferably, 0.75 g / m 2 ≤ρ1≤1.40g / m 2 When the surface density ρ1 of the coating is within the above range, it is beneficial for the secondary battery to have both high energy density and high thermal safety performance, and it can also make the coating have a suitable average pore area, and it can also further improve the heat resistance and ion conductivity of the isolation membrane.
[0038] In any embodiment of the present application, optionally, 1.50 g / m 2 ≤ρ2≤4.50g / m 2 , more preferably, 2.00 g / m 2 ≤ρ2≤4.00g / m 2 When the surface density ρ2 of the porous substrate is within the above range, the porous substrate can have a suitable average pore area, which is also beneficial to improving the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0039] In any embodiment of the present application, the porosity of the separator is recorded as P1, and the porosity of the porous substrate is recorded as P2, then 0.4≤P2 / P1<1; optionally, 0.55≤P2 / P1≤0.85. When P2 / P1 is within the above range, it is beneficial for the secondary battery to have both high thermal safety performance and good cycle performance and kinetic performance.
[0040] In any embodiment of the present application, 20%≤P1≤60%, optionally, 25%≤P1≤45%. When the porosity P1 of the separator is within the above range, it is beneficial for the secondary battery to have both high thermal safety performance and good cycle performance and kinetic performance.
[0041] In any embodiment of the present application, 15%≤P2≤45%, optionally, 20%≤P2≤40%. When the porosity P2 of the porous substrate is within the above range, it is beneficial to improve the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0042] In any embodiment of the present application, the first filler includes at least one of inorganic particles and organic particles. Optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon oxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate and magnesium fluoride, and more optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, silicon oxide, titanium oxide, zinc oxide, cerium oxide and barium titanate; Optionally, the organic particles include at least one of polystyrene particles, polyacrylic wax particles, melamine formaldehyde resin particles, phenolic resin particles, polyester particles, polyimide particles, polyamide imide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyether sulfone particles, polyether ether ketone particles and polyaryletherketone particles.
[0043] In any embodiment of the present application, the content of the fibrous material is ≤40wt%, and can be 5wt% to 25wt%, based on the total weight of the coating. When the content of the fibrous material is within the above range, the coating can have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the separator.
[0044] In any embodiment of the present application, the morphology of the fiber-like object optionally includes at least one of a rod-like, a tube-like, a rod-like, and a fiber-like.
[0045] In any embodiment of the present application, the average diameter of the fibrous material is ≤40 nm, and can be 10 nm to 35 nm. When the average diameter of the fibrous material is within the above range, it is helpful for the fibrous material to overlap with the filler to form an integrated effect.
[0046] In any embodiment of the present application, the average length of the fibrous material is 100 nm to 800 nm, and can be 200 nm to 600 nm. When the average length of the fibrous material is within a suitable range, the heat resistance and ion conductivity of the separator can be further improved.
[0047] In any embodiment of the present application, the aspect ratio of the fibrous material is 5 to 60, and can be 10 to 30. When the aspect ratio of the fibrous material is within a suitable range, the heat resistance and ion conductivity of the separator can be further improved.
[0048] In any embodiment of the present application, the fibrous material comprises at least one of an organic material and an inorganic material. Optionally, the organic material comprises at least one of nanocellulose, polytetrafluoroethylene nanofibers and polyamide nanofibers, and optionally, the nanocellulose comprises at least one of cellulose nanofibers, cellulose nanowhiskers and bacterial nanocellulose. Optionally, the inorganic material comprises at least one of halloysite nanotubes, nanorod-shaped aluminum oxide, nanorod-shaped boehmite, nanorod-shaped silicon oxide and glass fiber.
[0049] In any embodiment of the present application, the fibrous material comprises nanocellulose.
[0050] In any embodiment of the present application, the nanocellulose includes hydroxyl groups and anionic modification groups.
[0051] In any embodiment of the present application, the anion modification group includes at least one of an amine group, a carboxyl group, a sulfonic acid group, a boric acid group and a phosphoric acid group, and optionally includes at least one of a sulfonic acid group, a boric acid group and a phosphoric acid group. When the nanocellulose has the above-mentioned specific anion modification group, on the one hand, it can effectively improve the heat resistance of the isolation membrane and improve the thermal safety performance of the secondary battery; on the other hand, it can also improve the bonding strength between the coating and the porous substrate. When the nanocellulose has the above-mentioned specific anion modification group, it is also beneficial for the nanocellulose to overlap with the filler to form an integrated effect, thereby enabling the coating to have a more stable spatial network structure, thereby improving the isolation membrane's infiltration and retention characteristics of the electrolyte, improving the isolation membrane's ion conductivity and voltage breakdown resistance, and also helping to match high-voltage positive electrode active materials, and further improving the energy density of the secondary battery. In addition, the presence of anion modification groups can also reduce the proportion of hydroxyl groups, thereby ensuring that the coating slurry has a suitable viscosity, which is more conducive to coating, thereby also improving the production efficiency of the isolation membrane and the uniformity of the coating.
[0052] In any embodiment of the present application, the molar ratio of the anion-modified group to the hydroxyl group is 1:4 to 4:1, and can be 2:3 to 7:3. When the molar ratio of the anion-modified group to the hydroxyl group is within a suitable range, the heat resistance, ion conductivity, and electrolyte wetting and retention properties of the isolation membrane can be further improved.
[0053] In any embodiment of the present application, the coating further comprises a non-granular binder. Optionally, the non-granular binder comprises an aqueous solution binder.
[0054] In any embodiment of the present application, the content of the non-granular binder in the coating is ≤ 2 wt%, based on the total weight of the coating. The fibrous material and filler in the coating can form a stable spatial network structure, thereby enabling the isolation film to maintain high adhesion while reducing the amount of binder.
[0055] In any embodiment of the present application, the thickness of the porous substrate is ≤8 μm, and can be 3 μm to 6 μm. The coating of the present application can significantly improve the heat resistance of the separator, thereby allowing a thinner porous substrate to be used, thereby helping to improve the energy density of the secondary battery.
[0056] In any embodiment of the present application, the thickness of the coating is ≤2 μm, and can be optionally 0.5 μm to 1.3 μm. The coating of the present application has high heat resistance, thereby reducing the thickness of the coating and further improving the energy density of the secondary battery. In the present application, the thickness of the coating refers to the thickness of the coating located on one side of the porous substrate.
[0057] In any embodiment of the present application, the separator further comprises an adhesive layer, the adhesive layer is disposed on at least a portion of the surface of the coating, and the adhesive layer comprises a granular binder. The adhesive layer can not only prevent the coating from falling off and improve the safety performance of the secondary battery, but also improve the interface between the separator and the electrode and improve the cycle performance of the secondary battery.
[0058] In any embodiment of the present application, the granular binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer.
[0059] In any embodiment of the present application, the longitudinal heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤6%, and can be optionally 0.5% to 4%.
[0060] In any embodiment of the present application, the transverse heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤6%, and can be optionally 0.5% to 4%.
[0061] The separator of the present application has low thermal shrinkage in both the transverse and longitudinal directions at a high temperature of 150° C., thereby improving the safety performance of the secondary battery.
[0062] In any embodiment of the present application, the ion conductivity of the isolation membrane is ≥0.6ms / cm 2 , can be selected as ≥0.9ms / cm 2 The separator of the present application has high ion conductivity, thereby improving the cycle performance and / or kinetic performance of the secondary battery.
[0063] In any embodiment of the present application, the resistance value of the isolation film is ≤1.3Ω, and can be ≤1.0Ω. The isolation film of the present application has a low resistance value, thereby improving the cycle performance and / or kinetic performance of the secondary battery.
[0064] In any embodiment of the present application, the longitudinal tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0065] In any embodiment of the present application, the transverse tensile strength of the separator is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0066] The separator of the present application has high tensile strength in both the transverse and longitudinal directions, so that when the secondary battery expands, the probability of the separator being damaged is low, thereby improving the safety performance of the secondary battery.
[0067] In any embodiment of the present application, the wetted length of the isolation film is ≥30 mm, and can be optionally 30 mm to 80 mm.
[0068] In any embodiment of the present application, the wetting speed of the isolation film is ≥3 mm / s, and can be optionally 3 mm / s to 10 mm / s.
[0069] The separator of the present application has good wettability and retention properties for the electrolyte, thereby improving the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0070] In any embodiment of the present application, the air permeability of the separator is ≤300s / 100mL, and can be 100s / 100mL to 230s / 100mL. The separator of the present application has good air permeability, thereby improving ion conductivity and secondary battery capacity performance.
[0071] The second aspect of the present application provides a method for preparing the isolation membrane of the first aspect of the present application, comprising the following steps: providing a porous substrate; mixing the fibrous material and the filler in a solvent in a predetermined proportion, and then stirring them evenly at a certain shear rate to prepare a coating slurry; applying the coating slurry on at least one surface of the porous substrate, and obtaining an isolation membrane after drying, wherein the isolation membrane comprises a porous substrate and a coating arranged on at least one surface of the porous substrate, the coating comprising fibrous material and a filler; the filler comprises a first filler and a second filler, and the average particle size of the second filler is larger than the average particle size of the first filler.
[0072] In any embodiment of the present application, the shear rate is ≤30 m / s, and can be 15 m / s to 30 m / s. When the shear rate is within the above range, the dried coating can have a suitable average pore area, and the heat resistance and ion conductivity of the separator can be further improved.
[0073] In any embodiment of the present application, the solid content of the coating slurry is 8% to 30%, and optionally 10% to 20%.
[0074] In any embodiment of the present application, the coating surface density of one side of the coating slurry is 0.50 g / m 2 Up to 1.50g / m 2 , optional 0.75g / m 2 Up to 1.40g / m 2 When the coating surface density of the coating slurry is within the above range, the dried coating can have a suitable average pore area, and the heat resistance and ion conductivity of the separator can be further improved.
[0075] In any embodiment of the present application, the coating thickness of the coating slurry on one side is ≤2 μm, and can be 0.5 μm to 1.3 μm. When the coating thickness of the coating slurry is within the above range, the dried coating can have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the isolation membrane.
[0076] In any embodiment of the present application, the method further comprises the following steps: applying a slurry containing a granular binder on at least a portion of the surface of the coating layer, and forming an adhesive layer after drying.
[0077] A third aspect of the present application provides a secondary battery, comprising the isolation film of the first aspect of the present application or the isolation film prepared by the method of the second aspect of the present application.
[0078] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application.
[0079] The isolation membrane of the present application enables the secondary battery to have high energy density, high thermal safety performance, and good cycle performance and dynamic performance. The electrical device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0081] Figure 1 It is a schematic diagram of one embodiment of the secondary battery of the present application.
[0082] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a secondary battery.
[0083] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0084] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0085] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0086] Figure 6 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.
[0087] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are explained as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION
[0088] Hereinafter, the isolation membrane of the present application, its preparation method, and the embodiments of the related secondary battery and electrical device are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0089] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0090] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0091] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0092] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0093] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0094] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0095] If not otherwise specified, in this application, the terms "first", "second", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.
[0096] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.
[0097] Unless otherwise specified, the values of the parameters mentioned in the present application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of the present application.
[0098] Typically, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. Its main function is to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass freely to form a loop.
[0099] With the application and promotion of secondary batteries, people have higher and higher requirements for the energy density and dynamic performance of secondary batteries. Thinning the isolation membrane is an effective measure to improve the energy density of secondary batteries. The isolation membranes currently used in commercial secondary batteries are usually polyolefin porous membranes, such as polyethylene porous membranes, polypropylene porous membranes, or polypropylene / polyethylene / polypropylene three-layer composite membranes, with a melting point between 130°C and 160°C. Therefore, when its thickness is reduced, the heat resistance of the isolation membrane becomes worse, and a significant thermal shrinkage effect will occur when heated, causing the positive and negative electrodes inside the battery to directly contact, resulting in an internal short circuit, thereby increasing the safety risk of secondary batteries.
[0100] In order to solve the above problems, the current measures mainly include coating a heat-resistant inorganic ceramic layer on the polyolefin porous membrane, which can increase the mechanical strength of the separator, reduce the shrinkage of the separator when heated, and reduce the risk of short circuit between the positive and negative electrodes in the battery. However, the inventors found in further research that the inorganic ceramic layer has limited effect on improving the heat resistance of the separator, and in order to ensure that the separator has high heat resistance, it is necessary to increase the coating thickness of the inorganic ceramic layer, but this will extend the active ion transmission distance, affect the cycle performance and kinetic performance of the secondary battery, and also fail to balance the energy density of the secondary battery.
[0101] Therefore, it is often difficult for the isolation membranes in the prior art to enable secondary batteries to have high energy density, high thermal safety performance, and good cycle performance and kinetic performance.
[0102] Isolation film
[0103] Specifically, a first aspect of the embodiments of the present application provides an isolation membrane.
[0104] The isolation membrane includes a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein the coating includes fibers and fillers; the fillers include a first filler and a second filler, wherein the average particle size of the second filler is greater than the average particle size of the first filler.
[0105] In the process of studying the heat resistance of the isolation membrane, the inventors found that the heat resistance of the coating on the surface of the current porous substrate (such as an inorganic ceramic layer, etc.) is poor. In order to ensure that the coating has high heat resistance, it is usually necessary to increase the thickness of the coating, but this will result in the loss of the energy density, cycle performance and kinetic performance of the secondary battery.
[0106] The coating includes a fibrous substance and a filler, which helps the filler and the fibrous substance to form a nesting effect, thereby increasing the heat resistance of the separator, reducing the shrinkage of the separator when heated, reducing the risk of short circuit between the positive and negative electrodes, and making the secondary battery have high thermal safety performance, and maintaining high bonding strength between the coating and the porous substrate to prevent the filler from falling off during the long-term charging and discharging of the secondary battery. In addition, when at least a portion of the filler is filled in the three-dimensional skeleton structure formed by the fibrous substance, there are more contact sites between the filler and the fibrous substance, thereby reducing the amount of binder used in the coating, thereby effectively reducing the risk of binder pore blocking, and further improving the cycle performance and dynamic performance of the secondary battery. In some embodiments, at least a portion of the filler is filled in the three-dimensional skeleton structure formed by the fibrous material, and other portions of the filler may be located on the surface of the three-dimensional skeleton structure and / or the interface between the three-dimensional skeleton structure and the porous substrate. In addition, a small portion of the filler may be embedded in the porous substrate at the interface between the three-dimensional skeleton structure and the porous substrate. For example, during the winding process of the electrode assembly, a small portion of the filler at the interface may be embedded in the matrix and / or pores of the porous substrate due to external pressure.
[0107] The second filler has a larger particle size, which can better play its supporting role in the coating, reduce the shrinkage of the first filler, and reduce the amount of binder, thereby improving the heat resistance of the isolation membrane; the second filler has a larger particle size, which helps to make the coating have more pore structure and less water content when the amount used is small, thereby further improving the ion conductivity of the isolation membrane and the wetting and retention characteristics of the electrolyte.
[0108] In some embodiments, the average particle size of the first filler is 15 nm to 150 nm, optionally 15 nm to 150 nm, or 15 nm to 120 nm.
[0109] The first filler has the advantages of a small average particle size, a large specific surface area, and good affinity with fibrous materials, so that it can be better overlapped with the fibrous materials, so that the coating has a more stable spatial network structure, thereby increasing the ion conductivity of the isolation membrane, and improving the heat resistance of the isolation membrane and the infiltration and retention characteristics of the electrolyte, and thus the secondary battery using the isolation membrane of the present application can take into account high thermal safety performance, long service life, and good cycle performance and kinetic performance. In addition, when the average particle size of the first filler is within the above range, it can also make the coating have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the isolation membrane.
[0110] In some embodiments, the first filler includes primary particles or secondary particles formed from primary particles.
[0111] In some embodiments, the average particle size of the primary particles is 15 nm to 80 nm, optionally 20 nm to 80 nm, 30 nm to 75 nm.
[0112] In some embodiments, the average particle size of the secondary particles is 50 nm to 150 nm, optionally 50 nm to 135 nm, 50 nm to 120 nm, 55 nm to 150 nm, 55 nm to 135 nm, 55 nm to 120 nm.
[0113] In some embodiments, the first filler includes inorganic particles, and the crystal form of the inorganic particles includes at least one of the θ crystal form, the γ crystal form, and the η crystal form. Optionally, the crystal form of the inorganic particles includes at least one of the θ crystal form and the γ crystal form.
[0114] The inorganic particles of the θ crystal form have diffraction peaks at 2θ of 36.68°±0.2° and 31.21°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer. In some embodiments, the content of the inorganic particles of the θ crystal form in the first filler may be ≥50wt%, optionally 60wt% to 82wt%, based on the total weight of the inorganic particles in the first filler.
[0115] The γ-crystalline inorganic particles have diffraction peaks at 2θ of 66.95°±0.2° and 45.91°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer. In some embodiments, the content of the γ-crystalline inorganic particles in the first filler may be ≥10wt%, optionally 17wt% to 38wt%, based on the total weight of the inorganic particles in the first filler.
[0116] The η-crystal inorganic particles have diffraction peaks at 2θ of 31.89°±0.2° and 19.37°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer. In some embodiments, the content of the η-crystal inorganic particles in the first filler may be ≤5wt%, optionally ≤1.5wt%, and more optionally ≤1wt%, based on the total weight of the inorganic particles in the first filler.
[0117] The inorganic particles of the θ crystal form have a moderate specific surface area and hardness, thereby being able to better improve both the heat resistance and ion conductivity of the isolation membrane; the inorganic particles of the γ crystal form and the η crystal form have the advantage of a large specific surface area.
[0118] Selecting first fillers of different crystal types helps to improve at least one of the heat resistance, ion conductivity, and electrolyte wetting and retention properties of the separator.
[0119] In some embodiments, the first filler may include inorganic particles, and the crystal forms of the inorganic particles include θ crystal form, γ crystal form and η crystal form, and the content of the θ crystal form inorganic particles in the first filler may be 60wt% to 82wt%, the content of the γ crystal form inorganic particles may be 17wt% to 38wt%, and the content of the η crystal form inorganic particles may be ≤1.5wt%, all based on the total weight of the inorganic particles in the first filler.
[0120] The X-ray diffraction spectrum of inorganic particles can be obtained by testing as follows: After drying the inorganic particles, grind them in a mortar (such as an agate mortar) for 30 minutes, and then use an X-ray diffractometer (such as Miniflex600-C) to test and obtain the X-ray diffraction spectrum. The test can use a Cu target, a Ni filter, a tube voltage of 40KV, a tube current of 15mA, and a continuous scanning range of 5°-80°.
[0121] In some embodiments, the first filler may include inorganic particles, and the inorganic particles can be prepared as follows: a precursor solution of the inorganic particles is subjected to an oxidation reaction by high-pressure sputtering, and then heated at 600°C to 900°C (for example, 1 hour to 3 hours) to form inorganic particles with a primary particle morphology, and then dried and shaped at 150°C to 250°C (for example, 30 minutes to 60 minutes) to obtain inorganic particles with a secondary particle morphology after self-assembly of the primary particles.
[0122] In some embodiments, the BET specific surface area of the first filler is ≥15 m 2 / g, optional 18m 2 / g to 65m 2When the BET specific surface area of the first filler is within the above range, the coating can have a suitable average pore area, and the heat resistance and ion conductivity of the isolation membrane can be further improved; in addition, the affinity between the first filler and the fibrous material can be improved, so that the coating has a more stable spatial network structure, and the isolation membrane has better heat resistance and higher ion conductivity.
[0123] In some embodiments, the content of the first filler is ≥55wt%, and can be 60wt% to 90wt%, based on the total weight of the coating. When the content of the first filler is within the above range, the coating can have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the isolation membrane; in addition, it is also beneficial for the coating to have a more stable spatial network structure, thereby further improving the heat resistance and ion conductivity of the isolation membrane.
[0124] In some embodiments, the average particle size of the second filler is less than or equal to 400nm, and can be optionally 100nm to 300nm. When the average particle size of the second filler is within the above range, the coating can have a suitable average pore area, and the heat resistance and ion conductivity of the isolation membrane can be further improved; in addition, the supporting role of the second filler can be better exerted, the moisture content of the coating can be reduced, and the coating can maintain a stable pore structure during long-term charge and discharge, which is beneficial to ion transmission and can also improve the heat resistance of the isolation membrane.
[0125] In some embodiments, the BET specific surface area of the second filler is ≤15 m 2 / g, optional 7m 2 / g to 12m 2 / g. When the BET specific surface area of the second filler is within the above range, the coating can have a suitable average pore area, and the heat resistance and ion conductivity of the separator can be further improved; in addition, the supporting role of the second filler can be better exerted, the moisture content of the coating can be reduced, and the coating can maintain a stable pore structure during long-term charge and discharge, which is beneficial to ion transmission and can also improve the heat resistance of the separator.
[0126] In some embodiments, the second filler includes at least one of inorganic particles and organic particles.
[0127] In some embodiments, the inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of electrochemical reactions.
[0128] Optionally, the inorganic particles having a dielectric constant of 5 or more include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT), and at least one of their respective modified inorganic particles. Optionally, the modification method of each inorganic particle may be chemical modification and / or physical modification. The chemical modification method includes coupling agent modification (for example, using silane coupling agent, titanate coupling agent, etc.), surfactant modification, polymer grafting modification, etc. The physical modification method may be mechanical force dispersion, ultrasonic dispersion, high energy treatment, etc. The modification treatment can reduce the agglomeration of inorganic particles, thereby enabling the coating to have a more stable and uniform spatial network structure; in addition, by selecting a coupling agent, surfactant or polymer with a specific functional group to modify the inorganic particles, it is also helpful to improve the coating's wetting and retention characteristics for the electrolyte and improve the coating's adhesion to the porous substrate.
[0129] Optionally, the inorganic particles having ion conductivity but not storing ions include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, Lithium Aluminum Titanate Phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum titanate lithium Li x4 La y4 TiO3, Lithium Germanium Phosphate Thiophosphate x5 Ge y5 P z2 S w 、Lithium Nitride Li x6 N y6 、SiS2 glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4At least one of 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion conductivity of the isolation membrane.
[0130] Optionally, the inorganic particles capable of undergoing electrochemical reaction include at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials and lithium-titanium compounds.
[0131] In some embodiments, the organic particles include but are not limited to at least one of polyethylene particles, polypropylene particles, cellulose, cellulose modifiers (e.g., carboxymethyl cellulose), melamine resin particles, phenolic resin particles, polyester particles (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), silicone resin particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles, polyaryletherketone particles, and copolymers of butyl acrylate and ethyl methacrylate (e.g., cross-linked polymers of butyl acrylate and ethyl methacrylate).
[0132] In some embodiments, the second filler has a primary particle morphology.
[0133] In some embodiments, the second filler includes inorganic particles in the form of primary particles, and the crystal form of the inorganic particles in the form of primary particles includes at least one of α crystal form and γ crystal form, and optionally includes α crystal form. The α crystal form of the second filler has the advantages of high hardness, good heat resistance, low dielectric constant, high safety and high true density, thereby further improving the heat resistance of the coating.
[0134] In some embodiments, the second filler includes inorganic particles with a primary particle morphology, and the crystal form of the inorganic particles with a primary particle morphology includes an α-crystal form, and the content of the inorganic particles with an α-crystal form is ≥80wt%, optionally 85wt% to 100wt%, 90wt% to 100wt%, 95wt% to 100wt%, based on the total weight of the inorganic particles with a primary particle morphology in the second filler.
[0135] The inorganic particles of the α-crystal form have diffraction peaks at 2θ of 57.48°±0.2° and 43.34°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer.
[0136] In some embodiments, the content of the second filler is ≤20wt%, and can be 2wt% to 15wt%, based on the total weight of the coating. When the content of the second filler is within the above range, the coating can have a suitable average pore area, and the heat resistance and ion conductivity of the isolation membrane can be further improved; in addition, the supporting role of the second filler can be better exerted, the moisture content of the coating can be reduced, and the coating can maintain a stable pore structure during long-term charge and discharge, which is beneficial to ion transmission, and can also improve the heat resistance of the isolation membrane.
[0137] In some embodiments, along the thickness direction of the isolation membrane, the average pore area of the coating is smaller than the average pore area of the porous substrate;
[0138] The average pore area of the coating refers to the ratio of the total pore area of the coating in the cross-sectional image of the isolation membrane to the number of pores in the coating;
[0139] The average pore area of the porous substrate refers to the ratio of the total pore area of the porous substrate in the cross-sectional image of the separator to the number of pores in the porous substrate.
[0140] The average pore area S1 of the coating is smaller than the average pore area S2 of the porous substrate, thereby making the coating have high heat resistance; since the coating of the present application has high heat resistance, the thickness of the coating can be reduced (for example, the thickness of the coating can be less than or equal to 2 μm), shortening the active ion transmission distance, and thus the secondary battery can also take into account high energy density and good cycle performance and kinetic performance; in addition, since the coating of the present application has high heat resistance, a thinner porous substrate can be selected, thereby further improving the energy density of the secondary battery.
[0141] The inventors also found in further research that the ratio S1 / S2 of the average pore area S1 of the coating to the average pore area S2 of the porous substrate should not be too small. When S1 / S2 is too small, the average pore area of the coating is often small, which may hinder the transmission of active ions and affect the cycle performance and / or kinetic performance of the secondary battery. In some embodiments, 0.06≤S1 / S2<1, optionally, 0.10≤S1 / S2≤0.99, 0.20≤S1 / S2≤0.98, 0.30≤S1 / S2≤0.97, 0.30≤S1 / S2≤0.80, 0.30≤S1 / S2≤0.70, 0.35≤S1 / S2≤0.94, 0.35≤S1 / S2≤0.85, 0.40≤S1 / S2≤0.92, 0.40≤S1 / S2≤0.80, 0.40≤S1 / S2≤0.70, 0.45≤S1 / S2≤0.90.
[0142] In some embodiments, the average pore area S1 of the coating satisfies 0.0002 μm2 ≤S1≤0.0080μm 2 , optionally, 0.0004 μm 2 ≤S1≤0.0050μm 2 , 0.0008μm 2 ≤S1≤0.0048μm 2 When the average pore area S1 of the coating is within the above range, the heat resistance of the separator can be improved on the one hand, and the active ion transmission will not be hindered on the other hand, thereby enabling the secondary battery to better balance high energy density, high thermal safety performance, and good cycle performance and kinetic performance.
[0143] In some embodiments, the average pore area S2 of the porous substrate satisfies 0.0005 μm 2 ≤S2≤0.0100μm 2 , optionally, 0.0008 μm 2 ≤S2≤0.0080μm 2 When the average pore area S2 of the porous substrate is within the above range, it is beneficial to improve the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0144] In the present application, the average pore area S1 of the coating layer of the isolation membrane and the average pore area S2 of the porous substrate of the isolation membrane can be obtained by testing the cross-sectional image of the isolation membrane.
[0145] The average pore area S1 of the coating layer of the separator refers to the ratio of the total pore area of the coating layer in the cross-sectional image of the separator to the number of pores in the coating layer.
[0146] The average pore area S2 of the porous substrate of the separator refers to the ratio of the total pore area of the porous substrate in the cross-sectional image of the separator to the number of pores in the porous substrate.
[0147] In the present application, the cross-sectional image of the isolation membrane is an image along the thickness direction of the isolation membrane. A sample of the isolation membrane to be tested of a certain size (e.g., 15 mm × 15 mm) can be cut out from any area of the isolation membrane, and the isolation membrane cross section can be obtained by cutting with an ion beam polisher (e.g., Hitachi Arblade 5000) under freezing conditions (e.g., -80°C); referring to JY / T010-1996, a scanning electron microscope (e.g., Sigma 300 scanning electron microscope of ZEISS, Germany) is used to scan and obtain a SEM image of the isolation membrane cross section (the magnification can be 1000 to 30,000 times); an image processing detection system (e.g., Yihong isolation membrane detection system 2022-0408) is used to obtain the average pore area S1 of the isolation membrane coating and the average pore area S2 of the porous substrate of the isolation membrane using a multi-segment binarization method.
[0148] When using an ion beam polisher for cutting, the test sample can be wrapped with copper foil or aluminum foil before cutting. When obtaining a SEM image of the isolation film cross section, the test sample can be subjected to gold spraying.
[0149] Using the image processing detection system, the pore area data of the isolation membrane coating and the porous substrate can be obtained respectively, and then the pore area distribution diagram and the average pore area of the isolation membrane coating and the porous substrate can be obtained respectively through the Mintab software. The ratio of the total pore area of the isolation membrane coating to the number of pores in the coating is the average pore area S1 of the isolation membrane coating, and the ratio of the total pore area of the isolation membrane's porous substrate to the number of pores in the porous substrate is the average pore area S2 of the isolation membrane's porous substrate.
[0150] In some embodiments, the average pore size of the isolation membrane is denoted as d1, and the average pore size of the porous substrate is denoted as d2, then d1 / d2<1, optionally, 0.2≤d1 / d2≤0.9, 0.3≤d1 / d2≤0.8, 0.4≤d1 / d2≤0.7. When the ratio d1 / d2 of the average pore size d1 of the isolation membrane to the average pore size d2 of the porous substrate is within the above range, the isolation membrane can have a high ion conductivity while ensuring high heat resistance.
[0151] In some embodiments, the average pore size d1 of the isolation membrane satisfies 15nm≤d1≤50nm, and optionally, 20nm≤d1≤40nm. When the average pore size d1 of the isolation membrane is within the above range, on the one hand, the heat resistance of the isolation membrane can be improved, and on the other hand, the active ion transmission will not be hindered, thereby enabling the secondary battery to better balance high energy density, high thermal safety performance, and good cycle performance and kinetic performance.
[0152] In some embodiments, the average pore size d2 of the porous substrate satisfies 25nm≤d2≤60nm, optionally, 30nm≤d2≤50nm. When the average pore size d2 of the porous substrate is within the above range, it is beneficial to improve the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0153] The average pore size d1 of the isolation membrane and the average pore size d2 of the porous substrate can be tested using a capillary porosity tester (bubble point method). An exemplary test method is as follows: take a circular sample with a diameter of 25 mm, and drop 3-5 drops of infiltration liquid on it. After the sample is completely infiltrated, put it into a mold, and then use an inert gas to squeeze the pore infiltration liquid in the sample to be tested. The extrusion gas pressure and flow rate are inversely proportional to the pore size. The average pore size of the sample to be tested is obtained through software sampling and pressure and pore size conversion analysis. The test instrument can be PMI's CFP 1500 pore size analyzer, and the test pressure can be 100psi to 350psi.
[0154] In some embodiments, the surface density of the coating is denoted as ρ1, and the surface density of the porous substrate is denoted as ρ2, then 0.15≤ρ1 / ρ2≤0.80, optionally, 0.20≤ρ1 / ρ2≤0.50. When ρ1 / ρ2 is within the above range, it is beneficial for the coating to have high heat resistance, and it is also beneficial for the secondary battery to have both high energy density and high thermal safety performance.
[0155] In some embodiments, the surface density ρ1 of the coating satisfies 0.50 g / m 2 ≤ρ1≤1.50g / m 2 , optionally, 0.60 g / m 2 ≤ρ1≤1.40g / m 2 , 0.75g / m 2 ≤ρ1≤1.40g / m 2 , 0.75g / m 2 ≤ρ1≤1.30g / m 2 . When the surface density ρ1 of the coating is within the above range, it is beneficial for the secondary battery to have both high energy density and high thermal safety performance. When the surface density ρ1 of the coating is within the above range, the coating can also have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the isolation membrane. In the present application, the surface density of the coating refers to the surface density of the coating located on one side of the porous substrate.
[0156] In some embodiments, the surface density ρ2 of the porous substrate satisfies 1.50 g / m 2 ≤ρ2≤4.50g / m 2 , optionally, 2.00 g / m 2 ≤ρ2≤4.00g / m 2 When the surface density ρ2 of the porous substrate is within the above range, the porous substrate can have a suitable average pore area, which is also beneficial to improving the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0157] In some embodiments, the porosity of the isolation membrane is recorded as P1, and the porosity of the porous substrate is recorded as P2, then 0.4≤P2 / P1<1; optionally, 0.55≤P2 / P1≤0.85. When P2 / P1 is within the above range, it is beneficial for the secondary battery to have both high thermal safety performance and good cycle performance and kinetic performance.
[0158] In some embodiments, the porosity P1 of the separator satisfies 20%≤P1≤60%, optionally, 25%≤P1≤45%. When the porosity P1 of the separator is within the above range, it is beneficial for the secondary battery to have both high thermal safety performance and good cycle performance and dynamic performance.
[0159] In some embodiments, the porosity P2 of the porous substrate satisfies 15%≤P2≤45%, and optionally, 20%≤P2≤40%. When the porosity P2 of the porous substrate is within the above range, it is beneficial to improve the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0160] The porosity P1 of the isolation membrane and the porosity P2 of the porous substrate can be tested with reference to GB / T 24586-2009. The test method is as follows: punch the isolation membrane or porous substrate into small disc samples with a diameter of 14 mm, test the thickness, and calculate the apparent volume V1 of the isolation membrane or porous substrate according to the cylinder volume calculation formula; refer to GB / T24586-2009, use inert gas such as helium or nitrogen as the medium, adopt the gas replacement method, and use a true density tester to measure the true volume V2 of the isolation membrane or porous substrate. Then the porosity of the isolation membrane or porous substrate = (V1-V2) / V1×100%. The test instrument can be the AccuPyc II 1340 fully automatic true density tester of Micromeritics, USA.
[0161] In some embodiments, the thickness of the porous substrate is ≤8 μm, and can be 3 μm to 6 μm. The coating of the present application can significantly improve the heat resistance of the separator, thereby allowing a thinner porous substrate to be used, thereby helping to improve the energy density of the secondary battery.
[0162] In some embodiments, the thickness of the coating is ≤2 μm, and can be 0.5 μm to 1.3 μm. The coating of the present application has high heat resistance, thereby reducing the thickness of the coating and further improving the energy density of the secondary battery. In the present application, the thickness of the coating refers to the thickness of the coating on one side of the porous substrate.
[0163] The present application has no particular restrictions on the material of the porous substrate, and any known substrate with good chemical stability and mechanical stability can be selected. For example, the porous substrate may include at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The porous substrate may be a single-layer film or a multi-layer composite film. When the porous substrate is a multi-layer composite film, the materials of each layer may be the same or different.
[0164] In some embodiments, the first filler includes at least one of inorganic particles and organic particles, optionally including inorganic particles, or a combination of inorganic particles and organic particles. Inorganic particles have the characteristics of high hardness, high thermal stability and not easy to decompose, and their surface usually has hydroxyl groups, which makes it easy to build a stable spatial network structure with fibrous materials (such as nanocellulose, etc.). Organic particles have good thermal stability and are not easy to decompose. At the same time, when the internal temperature of the secondary battery reaches the melting point of the organic particles due to overcharge abuse, thermal abuse, etc., the organic particles can also melt and be sucked into the micropores of the porous substrate due to capillary action to play the role of closed holes and circuit breakers, which is beneficial to improve the safety performance of the secondary battery.
[0165] Optionally, the inorganic particles include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3) and magnesium fluoride (MgF2) at least one. More optionally, the inorganic particles include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), silicon oxide SiO x (0<x≤2), at least one of titanium oxide (TiO2), zinc oxide (ZnO), cerium oxide (CeO2) and barium titanate (BaTiO3).
[0166] Optionally, the organic particles include at least one of polystyrene particles, polyacrylic wax particles, melamine formaldehyde resin particles, phenolic resin particles, polyester particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles and polyaryletherketone particles.
[0167] In some embodiments, the morphology of the fibrous material optionally includes at least one of a rod, a tube (e.g., a hollow tube), a rod, and a fiber. The material of the appropriate shape is conducive to the formation of a stable spatial network structure between the fibrous material and the filler, thereby further improving the heat resistance and ion conductivity of the isolation membrane. In the present application, "fibrous material" refers to a material with an aspect ratio of 5 or more.
[0168] In some embodiments, the average diameter of the fibrous material is ≤40nm, and can be optionally 10nm to 35nm. When the average diameter of the fibrous material is within the above range, it helps to overlap the fibrous material and the filler to form an integrated effect. And it can effectively avoid the following situation: when the average diameter of the fibrous material is too large, the mutual entanglement effect of the three-dimensional skeleton structure formed by it is insufficient, which may cause the heat resistance and voltage breakdown resistance of the isolation membrane to be not excellent enough. In the present application, "three-dimensional skeleton structure" refers to a structure with a three-dimensional spatial shape and a certain porosity, which can be formed by overlapping the materials constituting the three-dimensional skeleton structure.
[0169] In some embodiments, the average length of the fibrous material is 100nm to 800nm, optionally 200nm to 600nm. When the average length of the fibrous material is within a suitable range, the heat resistance and ion conductivity of the isolation membrane can be further improved. And the following situations can be effectively avoided: when the average length of the fibrous material is too short, the overlap effect between it and the filler is poor, the heat resistance of the coating deteriorates, and during the coating drying process, the three-dimensional skeleton structure formed by the fibrous material is also prone to collapse due to the lack of support from the filler, which can easily cause pore blocking problems, hinder ion transmission and water discharge, and thus may affect the thermal safety performance, cycle performance and dynamic performance of the secondary battery; when the average length of the fibrous material is too long, the coating slurry has a large viscosity and poor flow, which may affect the coating slurry coating, and then affect the quality of the coating, for example, it may affect the heat resistance and ion conductivity of the isolation membrane.
[0170] In some embodiments, the aspect ratio of the fibrous material is 5 to 60, and can be optionally 10 to 30. When the aspect ratio of the fibrous material is within a suitable range, the heat resistance and ion conductivity of the isolation membrane can be further improved. And the following situations can be effectively avoided: when the aspect ratio of the fibrous material is too small, the overlap effect between it and the filler is poor, the heat resistance of the coating deteriorates, and during the drying process of the coating, the three-dimensional skeleton structure formed by the fibrous material is prone to collapse due to the lack of support from the filler, which can easily cause pore blocking problems, hinder ion transmission and water discharge, and thus may affect the thermal safety performance, cycle performance and dynamic performance of the secondary battery; when the aspect ratio of the fibrous material is too large, this may cause the ion conductivity of the isolation membrane to decrease, and then the cycle performance and / or dynamic performance of the secondary battery to deteriorate.
[0171] The average length and average diameter of the fibrous material can be measured by the following method: a 3.6 mm × 3.6 mm sample is cut out from any area of the isolation film, and the microscopic morphology of the coating in the sample is mapped using a scanning electron microscope (e.g., ZEISS Sigma 300), and a high vacuum mode is selected, the working voltage is 3 kV, and the magnification is 30,000 times to obtain a SEM image; based on the obtained SEM image, multiple (e.g., more than 5) test areas are selected for length statistics, and the size of each test area is 0.5 μm × 0.5 μm, and then the average value of the length obtained from each test area is taken as the average length of the fibrous material; based on the obtained SEM image, multiple (e.g., more than 5) test areas are selected for diameter statistics using Nano Measurer particle size distribution statistical software, and the size of each test area is 0.5 μm × 0.5 μm, and then the average value of the diameter obtained from each test area is taken as the average diameter of the fibrous material.
[0172] In some embodiments, the fibrous material comprises at least one of an organic material and an inorganic material. As the fibrous material, as long as it has electrical insulation, electrochemical stability and stability to the electrolyte, there is no particular restriction on the material, and it can be either an organic material or an inorganic material.
[0173] In some embodiments, the organic material comprises at least one of nanocellulose, polytetrafluoroethylene nanofibers, and polyamide nanofibers. In some embodiments, the inorganic material comprises at least one of halloysite nanotubes, nanorod-shaped aluminum oxide, nanorod-shaped boehmite, nanorod-shaped silicon oxide, and glass fiber.
[0174] In some embodiments, the fibrous material includes nanocellulose. Optionally, the nanocellulose includes at least one of cellulose nanofibers (Cellulose nanofibrils, CNF, also known as nanofibrillated cellulose or microfibrillated cellulose), cellulose nanocrystals (CNC, also known as cellulose nanocrystals, nanocrystalline cellulose) and bacterial nanocellulose (Bacterial nanocellulose, BNC, also known as bacterial cellulose or microbial cellulose). Optionally, the nanocellulose includes cellulose nanowhiskers, which have the advantage of high crystallinity, thereby better improving the heat resistance of the isolation membrane.
[0175] Nanocellulose refers to the general term for cellulose with any dimension at the nanometer level (e.g., within 100nm), which has both the characteristics of cellulose and the characteristics of nanoparticles. Nanocellulose can be a polymer nanomaterial extracted from wood, cotton, etc. in nature by one or more means of chemistry, physics, biology, etc. It has the advantages of wide sources, low cost, biodegradability, high modulus, and high specific surface area. Therefore, it is an excellent substitute for traditional petrochemical resources and can effectively alleviate environmental pollution and petrochemical resource shortages. Nanocellulose also has good high temperature resistance and a small volume change after heating, which can improve the heat resistance of the isolation membrane; at the same time, compared with traditional inorganic ceramic particles, nanocellulose has a lower density, which can also reduce the weight of the secondary battery and improve the weight energy density of the secondary battery. In addition, the three-dimensional skeleton structure formed by nanocellulose can also have tiny nanopores to prevent current leakage, which can also enable the isolation membrane to take into account good electrolyte infiltration and retention characteristics and good voltage breakdown resistance.
[0176] In some embodiments, the nanocellulose includes hydroxyl groups and anionic modifying groups.
[0177] In some embodiments, the anion modifying group optionally includes at least one of an amine group, a carboxyl group, a sulfonic acid group, a boric acid group and a phosphate group, and more optionally includes at least one of a sulfonic acid group, a boric acid group and a phosphate group.
[0178] The inventors found in further research that when nanocellulose has the above-mentioned specific anionic modified groups, on the one hand, it can effectively improve the heat resistance of the separator and the thermal safety performance of the secondary battery; on the other hand, it can also improve the bonding strength between the coating and the porous substrate. When nanocellulose has the above-mentioned specific anionic modified groups, it is also beneficial for the nanocellulose and the filler to overlap to form an integrated effect, thereby enabling the coating to have a more stable spatial network structure, thereby improving the separator's infiltration and retention characteristics for the electrolyte, improving the separator's ion conductivity and voltage breakdown resistance, and also helping to match high-voltage positive electrode active materials, and further improving the energy density of the secondary battery. In addition, the presence of anionic modified groups can also reduce the proportion of hydroxyl groups, thereby ensuring that the coating slurry has a suitable viscosity, which is more conducive to coating, thereby also improving the production efficiency of the separator and the uniformity of the coating.
[0179] In some embodiments, the molar ratio of the anion-modified group to the hydroxyl group is 1:4 to 4:1, and can be optionally 2:3 to 7:3. When the molar ratio of the anion-modified group to the hydroxyl group is within a suitable range, the heat resistance, ion conductivity, and electrolyte wetting and retention characteristics of the isolation membrane can be further improved. And the following situations can be effectively avoided: when the molar ratio of the anion-modified group to the hydroxyl group is too small, the further improvement effect of the anion-modified group on the heat resistance and ion conductivity of the isolation membrane may not be obvious; when the molar ratio of the anion-modified group to the hydroxyl group is too large, the isolation membrane may have poor wetting and retention characteristics for the electrolyte, which may affect the cycle performance and / or kinetic performance of the secondary battery, and may also cause the heat resistance of the isolation membrane to decrease, which may also affect the improvement effect on the thermal safety performance of the secondary battery.
[0180] The type of anionic modified groups in nanocellulose can be determined by infrared spectroscopy. For example, the infrared spectrum of the material can be tested to determine the characteristic peaks contained therein, thereby determining the type of anionic modified groups. Specifically, the material can be analyzed by infrared spectroscopy using instruments and methods known in the art, for example, using an infrared spectrometer (such as the IS10 Fourier transform infrared spectrometer of Nicolet Corporation, USA), and tested according to the general rules of infrared spectroscopy analysis methods of GB / T 6040-2019.
[0181] In some embodiments, the fiber includes a sulfonic acid group, and the content of sulfur in the fiber is ≥0.1 wt %, optionally 0.2 wt % to 0.5 wt %, based on the total weight of the fiber.
[0182] The sulfur content in the fiber can be tested as follows: After drying the fiber, grind it in a mortar (such as an agate mortar) for 30 minutes, and then use an X-ray diffractometer (such as Miniflex600-C) to test it to obtain the sulfur content. The test can use a Cu target, a Ni filter, a tube voltage of 40KV, a tube current of 15mA, and a continuous scanning range of 5°-80°.
[0183] In some embodiments, the content of the fibrous material is ≤40wt%, and can be 5wt% to 25wt%, based on the total weight of the coating. When the content of the fibrous material is within the above range, the coating can have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the separator.
[0184] In some embodiments, the coating also includes a non-granular binder. The present application has no particular restrictions on the type of non-granular binder, and any known material with good adhesion can be selected. Optionally, the non-granular binder includes an aqueous solution binder, which has the advantages of good thermodynamic stability and environmental protection, thereby facilitating the preparation and coating of the coating slurry. As an example, the aqueous solution binder may include at least one of an aqueous solution type acrylic resin (e.g., acrylic acid, methacrylic acid, sodium acrylate monomer homopolymer or copolymer with other comonomers), polyvinyl alcohol (PVA), isobutylene-maleic anhydride copolymer and polyacrylamide.
[0185] In some embodiments, the content of the non-granular binder in the coating is ≤ 2 wt%, based on the total weight of the coating. The fibrous material and filler in the coating can form a stable spatial network structure, thereby enabling the isolation film to maintain high adhesion while reducing the amount of binder used.
[0186] In some embodiments, the isolation film further comprises an adhesive layer, the adhesive layer is disposed on at least a portion of the surface of the coating, and the adhesive layer comprises a granular binder. The adhesive layer can not only prevent the coating from falling off and improve the safety performance of the secondary battery, but also improve the interface between the isolation film and the electrode and improve the cycle performance of the secondary battery.
[0187] Optionally, the granular binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer. The comonomer includes but is not limited to at least one of the following: an acrylate monomer, an acrylic acid monomer, an olefin monomer, a halogen-containing olefin monomer, a fluoroether monomer, etc.
[0188] Optionally, the granular binder includes a vinylidene fluoride based polymer, such as a homopolymer of vinylidene fluoride monomer (VDF) and / or a copolymer of vinylidene fluoride monomer and a comonomer. The comonomer may be at least one of an olefin monomer, a fluorine-containing olefin monomer, a chlorine-containing olefin monomer, an acrylate monomer, an acrylic monomer, and a fluoroether monomer. Optionally, the comonomer may include at least one of trifluoroethylene (VF3), chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro (alkyl vinyl) ether (e.g., perfluoro (methyl vinyl) ether PMVE, perfluoro (ethyl vinyl) ether PEVE, perfluoro (propyl vinyl) ether PPVE), perfluoro (1,3-dioxole) and perfluoro (2,2-dimethyl-1,3-dioxole) (PDD).
[0189] In some embodiments, the longitudinal heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤6%, and can be optionally 0.5% to 4%.
[0190] In some embodiments, the transverse heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤6%, and can be optionally 0.5% to 4%.
[0191] The separator of the present application has low thermal shrinkage in both the transverse and longitudinal directions at a high temperature of 150° C., thereby improving the safety performance of the secondary battery.
[0192] In some embodiments, the ionic conductivity of the isolation membrane is ≥0.6 ms / cm 2 , can be selected as ≥0.9ms / cm 2 .
[0193] The separator of the present application has high ion conductivity, thereby being able to improve the cycle performance and / or kinetic performance of the secondary battery.
[0194] In some embodiments, the resistance value of the isolation film is ≤1.3Ω, and can be ≤1.0Ω.
[0195] The separator of the present application has a low resistance value, thereby being able to improve the cycle performance and / or kinetic performance of the secondary battery.
[0196] In some embodiments, the longitudinal tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0197] In some embodiments, the transverse tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0198] The separator of the present application has high tensile strength in both the transverse and longitudinal directions, so that when the secondary battery expands, the probability of the separator being damaged is low, thereby improving the safety performance of the secondary battery.
[0199] In some embodiments, the wetted length of the isolation film is ≥30 mm, and can be optionally 30 mm to 80 mm.
[0200] In some embodiments, the wetting speed of the isolation film is ≥3 mm / s, and can be optionally 3 mm / s to 10 mm / s.
[0201] The separator of the present application has good wettability and retention properties for the electrolyte, thereby improving the ion conductivity of the separator and the capacity performance characteristics of the secondary battery.
[0202] In some embodiments, the air permeability of the isolation membrane is ≤300s / 100mL, and can be optionally 100s / 100mL to 230s / 100mL.
[0203] The separator of the present application has good air permeability, thereby being able to improve ion conductivity and secondary battery capacity performance characteristics.
[0204] In the present application, the average particle size of a material (e.g., a first filler, a second filler) has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, a scanning electron microscope, a transmission electron microscope, or a particle size distribution instrument can be used to measure a material or a separator to obtain an image, and a plurality of (e.g., more than 10) test particles (e.g., having a first filler, a second filler) are randomly selected from the image, and the average value of the shortest diagonal length of the particles is calculated as the average particle size.
[0205] In the present application, the specific surface area of a material (e.g., a first filler, a second filler) is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by BET (BrunauerEmmett Teller) method. Alternatively, the nitrogen adsorption specific surface area analysis test can be performed by a Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0206] In the present application, the heat shrinkage, tensile strength and air permeability of the isolation film have the meanings known in the art and can be measured by methods known in the art. For example, they can be tested with reference to the standard GB / T 36363-2018.
[0207] In the present application, the wetting length and wetting speed of the isolation membrane have the meanings known in the art and can be measured by methods known in the art. An exemplary test method is as follows: cut the isolation membrane into samples with a width of 5 mm and a length of 100 mm, fix the two ends of the sample and place it horizontally; take 0.5 mg of electrolyte and drop it in the center of the sample. After reaching the specified time (1 min in this application), take a picture and measure the length of the electrolyte diffusion, thereby obtaining the wetting length and wetting speed of the isolation membrane. In order to ensure the accuracy of the test results, multiple (for example, 5 to 10) samples can be taken for testing, and the test results are obtained by calculating the average value. The electrolyte can be prepared as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of 30:50:20 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0208] The ion conductivity and resistance of the isolation membrane can be obtained by AC impedance spectroscopy test. Specifically, the isolation membrane is cut into discs of a certain area, dried, placed between two stainless steel electrodes, and sealed to form a button cell after absorbing a sufficient amount of electrolyte, and then the AC impedance spectroscopy test is carried out.
[0209] It should be noted that the coating parameters (such as surface density, thickness, etc.) of the above-mentioned isolation membrane are the coating parameters of one side of the porous substrate. When the coating is provided on both sides of the porous substrate, the coating parameters on either side satisfy the requirements of this application and are considered to fall within the protection scope of this application.
[0210] Preparation method
[0211] The second aspect of the embodiment of the present application provides a method for preparing the isolation membrane of the first aspect of the embodiment of the present application, comprising the following steps: providing a porous substrate; mixing a fibrous material and a filler in a solvent in a predetermined proportion, and then stirring evenly at a certain shear rate to prepare a coating slurry; applying the coating slurry on at least one surface of the porous substrate, and obtaining an isolation membrane after drying, wherein the isolation membrane comprises a porous substrate and a coating arranged on at least one surface of the porous substrate, the coating comprising a fibrous material and a filler; the filler comprises a first filler and a second filler, and the average particle size of the second filler is larger than the average particle size of the first filler.
[0212] In some embodiments, the solvent used in preparing the coating slurry may be water, such as deionized water.
[0213] In some embodiments, the coating slurry may further include other components, for example, a dispersant, a wetting agent, a binder, etc.
[0214] In some embodiments, the shear rate is ≤30 m / s, and can be 15 m / s to 30 m / s. When the shear rate is within the above range, the dried coating can have a suitable average pore area, and the heat resistance and ion conductivity of the isolation membrane can be further improved.
[0215] In some embodiments, the solid content of the coating slurry is 8% to 30%, and optionally 10% to 20%.
[0216] In some embodiments, the coating surface density of a single side of the coating slurry is 0.50 g / m 2 Up to 1.50g / m 2 , optional 0.75g / m 2 Up to 1.40g / m 2 When the coating surface density of the coating slurry is within the above range, the dried coating can have a suitable average pore area, and the heat resistance and ion conductivity of the separator can be further improved.
[0217] In some embodiments, the coating thickness of the coating slurry on one side is ≤2 μm, and can be 0.5 μm to 1.3 μm. When the coating thickness of the coating slurry is within the above range, the dried coating can have a suitable average pore area, and can further improve the heat resistance and ion conductivity of the isolation membrane.
[0218] In some embodiments, the fibrous material may include at least one of an organic material and an inorganic material. Optionally, the organic material includes at least one of nanocellulose, polytetrafluoroethylene nanofibers and polyamide nanofibers. Optionally, the inorganic material includes at least one of halloysite nanotubes, nanorod-shaped aluminum oxide, nanorod-shaped boehmite, nanorod-shaped silicon oxide and glass fiber. In some embodiments, the fibrous material may include nanocellulose, which may be cellulose nano whiskers (Cellulose nanocrystals, CNC, also known as cellulose nanocrystals, nanocrystalline cellulose).
[0219] In some embodiments, the nanocellulose can be obtained according to the following method: providing cellulose powder with a whiteness ≥ 80%; mixing and reacting the obtained cellulose powder with a modified solution, washing and removing impurities to obtain cellulose nano whiskers; adjusting the pH of the obtained cellulose nano whiskers to neutral, and obtaining nanocellulose by grinding and cutting.
[0220] Optionally, the cellulose powder with a whiteness of ≥80% can be purchased from the market, or obtained by chemical methods (such as acid hydrolysis, alkali treatment, Tempo catalytic oxidation), biological methods (such as enzyme treatment), mechanical methods (such as ultrafine grinding, ultrasonic crushing, high-pressure homogenization), etc. The fiber raw material used to prepare the cellulose powder with a whiteness of ≥80% can include plant fibers, such as cotton fibers (such as cotton fibers, kapok fibers), hemp fibers (such as sisal fibers, ramie fibers, jute fibers, flax fibers, hemp fibers, abaca fibers, etc.), palm fibers, wood fibers, bamboo fibers, and grass fibers.
[0221] In some embodiments, the cellulose powder with a whiteness of ≥80% can also be prepared by the following method: after the fiber raw material is loosened and deslagging, it is cooked with an alkali solution (for example, an aqueous solution of NaOH, whose concentration can be 4wt% to 20wt%, optionally 5wt% to 15wt%), and then sequentially washed with water to remove impurities (for example, the number of washings is 3 to 6 times), bleached (for example, sodium hypochlorite and / or hydrogen peroxide can be used), acid washed to remove impurities, washed with water to remove impurities, water driven, and air drying to obtain cellulose powder.
[0222] In some embodiments, the modification solution may be an acid solution (eg, aqueous sulfuric acid solution, aqueous boric acid solution, aqueous phosphoric acid solution, aqueous acetic acid solution) or an alkaline solution (eg, urea organic solvent solution). Optionally, the modification solution is an acid solution.
[0223] Optionally, the concentration of the acid solution may be 5wt% to 80wt%. When the modified solution is a sulfuric acid aqueous solution, the concentration of the acid solution may be 40wt% to 80wt%, thereby obtaining a cellulose powder having a sulfonic acid group. When the modified solution is a boric acid aqueous solution, the concentration of the acid solution may be 5wt% to 10wt%, thereby obtaining a cellulose powder having a boric acid group. When the modified solution is a phosphoric acid aqueous solution, the concentration of the acid solution may be 45wt% to 75wt%, thereby obtaining a cellulose powder having a phosphoric acid group. When the modified solution is an acetic acid aqueous solution, the concentration of the acid solution may be 40wt% to 80wt%, thereby obtaining a cellulose powder having a carboxylic acid group.
[0224] Optionally, the urea organic solvent solution is a urea xylene solution, thereby obtaining cellulose powder having amine groups.
[0225] In some embodiments, the mass ratio of the cellulose powder to the modified solution may be 1:2.5 to 1:50, and may be 1:5 to 1:30.
[0226] When the modification solution is a sulfuric acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:5 to 1:30. When the modification solution is a boric acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:20 to 1:50. When the modification solution is a phosphoric acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:5 to 1:30. When the modification solution is an acetic acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:5 to 1:30. When the modification solution is a urea organic solvent solution, the mass ratio of the cellulose powder to the urea organic solvent solution may be 1:4 to 1:40.
[0227] In some embodiments, when the modified solution is an acid solution, the reaction can be carried out at a temperature not higher than 80°C, optionally at 30°C to 60°C, and the reaction time of the cellulose powder and the modified solution can be 0.5h to 4h, optionally 1h to 3h.
[0228] In some embodiments, when the modified solution is an alkaline solution, the reaction may be performed at 100° C. to 145° C., and the reaction time of the cellulose powder and the modified solution may be 1 h to 5 h.
[0229] In some embodiments, grinding can be performed using a grinder, and cutting can be performed using a high-pressure homogenizer. Nanocellulose with different average diameters and / or different average lengths can be obtained by adjusting the grinding parameters (e.g., grinding times, grinding time, etc.) of the grinder and the cutting parameters of the high-pressure homogenizer.
[0230] In some embodiments, the coating slurry may be applied using a coater. The present application has no particular restrictions on the type of coater, for example, a commercially available coater may be used. The coater includes a gravure roller; the gravure roller is used to transfer the slurry to the porous substrate.
[0231] In some embodiments, the coating slurry may be applied by transfer coating, spin spray coating, dip coating, etc.
[0232] In some embodiments, the method further comprises the following steps: applying a slurry containing a granular binder on at least a portion of the surface of the coating layer, and forming an adhesive layer after drying.
[0233] The preparation method of the isolation film of the present application obtains the coating layer by one-time coating, which greatly simplifies the production process of the isolation film.
[0234] Some parameters such as raw materials and their contents used in the preparation method of the isolation membrane of the present application can refer to the isolation membrane of the first aspect of the implementation method of the present application, and will not be repeated here.
[0235] Unless otherwise specified, all raw materials used in the method for preparing the isolation membrane of the present application can be obtained commercially.
[0236] Secondary battery
[0237] A third aspect of the embodiments of the present application provides a secondary battery.
[0238] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can be recharged to activate active materials and continue to be used after the battery is discharged. Generally, secondary batteries include electrode assemblies and electrolytes. The electrode assemblies include positive electrode sheets, negative electrode sheets, and separators. The separators are arranged between the positive electrode sheets and the negative electrode sheets, and mainly play the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through.
[0239] The present application has no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium ion battery, a sodium ion battery, etc. In particular, the secondary battery may be a lithium ion secondary battery.
[0240] The secondary battery of the third aspect of the embodiment of the present application comprises the separator of the first aspect of the embodiment of the present application or the separator prepared by the method of the second aspect of the embodiment of the present application, and the separator is spaced between the positive electrode sheet and the negative electrode sheet. Optionally, at least one side of the separator close to the negative electrode sheet has the coating of the present application. Thus, the secondary battery of the present application can take into account high energy density, high thermal safety performance, and good cycle performance and kinetic performance.
[0241] [Positive electrode]
[0242] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0243] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include but is not limited to at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate and their respective modified compounds. Examples of the lithium transition metal oxide may include but are not limited to at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their respective modified compounds. Examples of the lithium-containing phosphate may include but are not limited to at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon and their respective modified compounds.
[0244] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from at least one of N, F, S and Cl.
[0245] As an example, the positive electrode active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.
[0246] When the secondary battery of the present application is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0247] As an example, the positive electrode active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x In the general formula X p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X is selected from H + , Li + 、Na + , K + and NH4 + At least one of, M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br.
[0248] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.
[0249] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the positive electrode film layer, the mass percentage of the positive electrode conductive agent is ≤5wt%.
[0250] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. The present application has no particular restrictions on the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total weight of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5wt%.
[0251] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0252] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0253] [Negative electrode]
[0254] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0255] The negative electrode active material may be a negative electrode active material for a secondary battery known in the art. As an example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material.
[0256] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5wt%.
[0257] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5wt%.
[0258] In some embodiments, the negative electrode film layer may further include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2wt%.
[0259] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0260] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0261] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0262] [Electrolyte]
[0263] During the charge and discharge process of the secondary battery, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs.
[0264] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.
[0265] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0266] When the secondary battery of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0267] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0268] In some embodiments, the electrolyte may further include additives, for example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.
[0269] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.
[0270] In some embodiments, the secondary battery may include an outer package, which may be used to package the electrode assembly and the electrolyte.
[0271] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0272] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0273] In some embodiments, Figure 2As shown, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0274] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and a secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0275] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0276] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0277] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0278] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0279] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0280] Electrical devices
[0281] The fourth aspect of the embodiment of the present application provides an electric device, which includes at least one of the secondary battery, battery module or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0282] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0283] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module can be used.
[0284] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0285] Example
[0286] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0287] Preparation of Nanocellulose C1
[0288] Cellulose powder preparation
[0289] The cotton linters were opened and deslagging by a cotton opener, and then boiled at 150°C for 2 hours using a 5wt% NaOH aqueous solution. The cotton linters were then washed with water to remove impurities (the number of washings was 3 times), bleached with sodium hypochlorite, washed with dilute hydrochloric acid to remove impurities, washed with water to remove impurities (the number of washings was 1 time), driven out of water, and dried with air flow to obtain cotton cellulose powder with a whiteness of ≥85%.
[0290] Esterification of cellulose
[0291] 1 kg of the obtained cotton cellulose powder was mixed with 30 kg of a 60 wt % sulfuric acid aqueous solution, and reacted at 55° C. to 60° C. for 1.5 h. After the reaction, the powder was washed with water for 3 times, filtered, and deacidified to obtain cellulose nano whiskers with sulfonic acid groups.
[0292] Neutralization of cellulose
[0293] The pH of the cellulose nanowhiskers with sulfonic acid groups was first adjusted to neutral with a 10wt% NaOH aqueous solution, then ground with a grinder, and then cut at the nanoscale using a high-pressure homogenizer to obtain nanocellulose with sulfonic acid modified groups with an average length of 500nm and an average diameter of 22nm, and the molar ratio of sulfonic acid groups to hydroxyl groups was 5:3.
[0294] The molar ratio of anionic modified groups to hydroxyl groups in nanocellulose can be measured by the following method: the hydroxyl values (milligrams of potassium hydroxide equivalent to the hydroxyl content in each gram of sample) of raw cellulose and nanocellulose are measured according to the phthalic anhydride method in GB / T12008.3-2009, and the numerical unit obtained is mg KOH / g, which is converted into mmol / g as the hydroxyl content. The content of anionic modified groups (i.e., the content of modified hydroxyl groups) can be obtained by subtracting the hydroxyl content of nanocellulose from the hydroxyl content of raw cellulose, and the molar ratio of anionic modified groups to hydroxyl groups can be calculated.
[0295] Preparation of Nanocellulose C2
[0296] Unmodified nanocellulose with an average length of 500 nm and an average diameter of 22 nm, product model CNWS-50, purchased from Zhongke Leiming (Beijing) Technology Co., Ltd., can be further processed using a grinder and / or a high-pressure homogenizer to obtain nanocellulose with different average diameters and / or different average lengths.
[0297] Example 1
[0298] Preparation of isolation membrane
[0299] Provide PE porous substrate: thickness 4.8μm, porosity 32%.
[0300] Preparation of coating slurry: The prepared nanocellulose C1, the first filler aluminum oxide (secondary particle morphology, average particle size of 75nm), and the binder aqueous solution type polyacrylic acid are mixed uniformly in an appropriate amount of solvent deionized water according to a mass ratio of 16:83:1, and then stirred at a shear rate of 23m / s to obtain a coating slurry with a solid content of 15wt%. The contents of α crystal, θ crystal, γ crystal and η crystal in the first filler are 1.1wt%, 68.7wt%, 29.6wt% and 0.6wt%, respectively, based on the total weight of the first filler.
[0301] Coating: The prepared coating slurry is coated on both surfaces of the PE porous substrate by a coating machine, and the isolation film is obtained through drying and slitting processes. The coating thickness on one side of the PE porous substrate is 0.8μm and the surface density is 1.25g / m 2 .
[0302] Preparation of positive electrode
[0303] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in a proper amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 96.2:2.7:1.1 to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.
[0304] Preparation of negative electrode
[0305] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0306] Preparation of electrolyte
[0307] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of 30:70 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0308] Preparation of secondary batteries
[0309] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a secondary battery is obtained.
[0310] Example 2-16
[0311] The secondary battery was prepared in a similar manner to Example 1, with the differences shown in Table 1. The second filler in Examples 12-15 was in primary particle morphology, and the crystal form of the second filler was mainly α crystal form, accounting for more than 99% by mass based on the total weight of the second filler.
[0312] Comparative Example 1
[0313] The secondary battery was prepared by a method similar to that of Example 1, except for the preparation process of the isolation membrane.
[0314] Provide PE porous substrate: thickness 4.8μm, porosity 32%.
[0315] Preparation of coating slurry: Alumina (average particle size of 600 nm, primary particle morphology, α crystal mass accounting for more than 99%) and a binder are mixed in a mass ratio of 94:6 and dissolved in deionized water, and then stirred at a shear speed of 23 m / s to obtain a coating slurry with a solid content of 38 wt%.
[0316] Coating: The prepared coating slurry is coated on both surfaces of the PE porous substrate by a coating machine, and the isolation film is obtained through drying and slitting processes. The coating thickness on one side of the PE porous substrate is 1.7μm and the surface density is 1.80g / m 2 .
[0317] Test Section
[0318] (1) Ion conductivity test of isolation membrane
[0319] The ionic conductivity of the isolation membrane is obtained by AC impedance spectroscopy experiment test. Specifically, the isolation membrane is cut into discs of a certain area, dried, placed between two stainless steel electrodes, and sealed to form a button battery after absorbing a sufficient amount of electrolyte. An AC impedance spectroscopy experiment is performed using an electrochemical workstation to obtain the ionic conductivity of the isolation membrane. The electrochemical workstation can use Shanghai Chenhua CHI 660C electrochemical workstation, the AC signal frequency range is 0.01Hz to 1MHz, and the sine wave potential amplitude is 5mV. For accuracy, the average value of 5 parallel samples is taken as the test result.
[0320] The electrolyte used is prepared as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of 30:50:20 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0321] (2) Average pore area test of coating and porous substrate
[0322] Cut out a test isolation membrane sample of a certain size (for example, 15 mm×15 mm) from an arbitrary area of the isolation membrane, wrap the isolation membrane sample with copper foil, and cut it under freezing conditions (for example, -80°C) using an ion beam polisher (for example, Hitachi Arblade 5000); spray gold on the isolation membrane sample, and then refer to JY / T010-1996 and use a scanning electron microscope (for example, Sigma 300 scanning electron microscope from ZEISS, Germany) to obtain a SEM image of the isolation membrane cross section (the magnification can be 1000 to 30,000 times); use an image processing detection system (for example, Yihong Isolation Membrane Detection System 2022-0408) to obtain the average pore area S1 of the coating of the isolation membrane and the average pore area S2 of the porous substrate of the isolation membrane using a multi-segment binarization method. The ratio of the total pore area of the coating of the isolation membrane to the number of pores in the coating is the average pore area S1 of the coating of the isolation membrane, and the ratio of the total pore area of the porous substrate of the isolation membrane to the number of pores in the porous substrate is the average pore area S2 of the porous substrate of the isolation membrane. For accuracy, the average value of 5 parallel samples is taken as the test result.
[0323] (3) Thermal shrinkage test of isolation film
[0324] Sample preparation: The isolation film prepared above was punched into samples with a width of 50 mm and a length of 100 mm using a punching machine. Five parallel samples were placed on A4 paper and fixed. The A4 paper containing the samples was then placed on corrugated paper with a thickness of 1 mm to 5 mm.
[0325] Sample test: Place the A4 paper on the corrugated paper into a blast oven, set the temperature of the blast oven to 150°C, and start timing after the temperature reaches the set temperature and stabilizes for 30 minutes. After the set time (1 hour in this application) is reached, measure the length and width of the isolation film, and the values are marked as a and b respectively.
[0326] Calculation of thermal shrinkage: longitudinal (MD) thermal shrinkage = [(100-a) / 100] × 100%, transverse (TD) thermal shrinkage = [(50-b) / 50] × 100%, and the average value of 5 parallel samples is taken as the test result.
[0327] (4) Thermal Box Test of Secondary Battery
[0328] At 25°C, charge the secondary battery at a constant current of 1C to 4.2V, continue constant voltage charging until the current is ≤0.05C, and let it stand for 5 min; then test each secondary battery with a fixture in a DHG-9070A DHG series high-temperature oven, raise the temperature from room temperature to 80°C ± 2°C at a rate of 5°C / min, and maintain for 30 min; then raise the temperature at a rate of 5°C / min again, and keep it warm for 30 min every time the temperature rises by 5°C. Monitor the surface temperature change of the secondary battery during the heating process. The oven temperature corresponding to when the temperature starts to rise sharply is the thermal box failure temperature of the secondary battery. The higher the thermal box failure temperature of the secondary battery, the better the thermal safety performance of the secondary battery. For accuracy, take the average value of 5 parallel samples as the test result.
[0329] (5) Cycle Performance Test of Secondary Battery
[0330] At 25°C, charge the secondary battery at a constant current of 1C to 4.2V, continue constant voltage charging until the current is ≤0.05C. At this time, the secondary battery is in a fully charged state, and record the charging capacity at this time, which is the charging capacity of the first cycle; after letting the secondary battery stand for 5 min, discharge it at a constant current of 1C to 2.8V. This is a cycle of charge and discharge process, and record the discharge capacity at this time, which is the discharge capacity of the first cycle. Perform cycle charge and discharge tests on the secondary battery according to the above method, and record the discharge capacity after each cycle. The capacity retention rate (%) of the secondary battery after 1000 cycles at 25°C = discharge capacity after 1000 cycles / discharge capacity of the first cycle × 100%. For accuracy, take the average value of 5 parallel samples as the test result.
[0331] As can be seen from Table 2, in Examples 1-16, by providing coatings containing nanocellulose (constituting a three-dimensional skeleton structure) and fillers on both surfaces of the porous substrate of the separator membrane, and reasonably controlling the average pore area S1 of the coating and the average pore area S2 of the porous substrate to satisfy 0 < S1 / S2 < 1, the separator membrane can have both low thermal shrinkage rate and high ion conductivity, and the secondary battery can also have both high thermal safety performance and good cycle performance.
[0332] It should be noted that this application is not limited to the above embodiments. The above embodiments are only examples. Embodiments having the same composition and the same effect as the technical idea within the technical solution scope of this application are all included in the technical scope of this application. In addition, within the scope of not departing from the gist of this application, various modifications that those skilled in the art can think of to the embodiments, and other ways constructed by combining some constituent elements in the embodiments are also included in the scope of this application.
[0333]
[0334] Table 2
[0335]
Claims
1. A separator comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein: The coating comprises fibers and fillers; the fillers comprise a first filler and a second filler, wherein the average particle size of the second filler is greater than the average particle size of the first filler.
2. The isolation film according to claim 1, wherein: The average particle size of the first filler is 15 nm to 150 nm, and can be 15 nm to 120 nm.
3. The isolation film according to claim 1 or 2, wherein: The average particle size of the second filler is 100 nm to 400 nm, and can be optionally 100 nm to 300 nm.
4. The isolation film according to any one of claims 1 to 3, wherein: The first filler includes primary particles or secondary particles formed from primary particles; Optionally, the average particle size of the first filler of the primary particle morphology is 15 nm to 80 nm, and optionally 30 nm to 75 nm; Optionally, the average particle size of the first filler in the secondary particle morphology is 50 nm to 150 nm, and optionally 55 nm to 120 nm.
5. The isolation film according to any one of claims 1 to 4, wherein: The first filler includes inorganic particles, and the crystal form of the inorganic particles includes at least one of the θ crystal form, the γ crystal form and the η crystal form; Optionally, the crystal form of the inorganic particles includes at least one of a θ crystal form and a γ crystal form; Optionally, the content of the inorganic particles of the θ crystal form is ≥50wt%, more preferably 60wt% to 82wt%, based on the total weight of the inorganic particles in the first filler; Optionally, the content of the γ-crystalline inorganic particles is ≥10 wt %, more preferably 17 wt % to 38 wt %, based on the total weight of the inorganic particles in the first filler; Optionally, the content of the η-crystal inorganic particles is ≤5 wt %, and more preferably ≤1.5 wt %, based on the total weight of the inorganic particles in the first filler.
6. The isolation film according to any one of claims 1 to 5, wherein: The BET specific surface area of the first filler is ≥15m 2 / g, optional 18m 2 / g to 65m 2 / g; and / or, The content of the first filler is ≥55 wt %, and can be optionally 60 wt % to 90 wt %, based on the total weight of the coating.
7. The isolation film according to claim 1-6, wherein: The second filler satisfies at least one of the following conditions (1) to (6): (1) The second filler has a primary particle morphology; (2) The BET specific surface area of the second filler is ≤15m 2 / g, optional 7m 2 / g to 12m 2 / g; (3) the content of the second filler is ≤ 20 wt %, and can be optionally 2 wt % to 15 wt %, based on the total weight of the coating; (4) the second filler comprises at least one of inorganic particles and organic particles; (5) The second filler comprises inorganic particles in the form of primary particles, and the crystal form of the inorganic particles in the form of primary particles comprises at least one of an α crystal form and a γ crystal form, and may optionally comprise an α crystal form; (6) The second filler includes inorganic particles with a primary particle morphology, and the crystal form of the inorganic particles with a primary particle morphology includes an α-crystal form, and the content of the inorganic particles with an α-crystal form is ≥80wt%, and can be optionally 90wt% to 100wt%, based on the total weight of the inorganic particles with a primary particle morphology in the second filler.
8. The isolation film according to any one of claims 1 to 7, wherein: Along the thickness direction of the isolation membrane, the average pore area of the coating is smaller than the average pore area of the porous substrate; The average pore area of the coating refers to the ratio of the total pore area of the coating in the cross-sectional image of the isolation membrane to the number of pores in the coating; The average pore area of the porous substrate refers to the ratio of the total pore area of the porous substrate in the cross-sectional image of the separator to the number of pores in the porous substrate.
9. The isolation film according to claim 8, wherein: Along the thickness direction of the isolation membrane, the average pore area of the coating is recorded as S1, and the average pore area of the porous substrate is recorded as S2, then 0.06≤S1 / S2<1, optionally, 0.30≤S1 / S2≤0.
97.
10. The isolation film according to claim 8 or 9, wherein: Along the thickness direction of the isolation membrane, the average pore area of the coating is recorded as S1, and the average pore area of the porous substrate is recorded as S2. 0.0002μm 2 ≤S1≤0.0080μm 2 , optionally, 0.0004 μm 2 ≤S1≤0.0050μm 2 ; and / or, 0.0005 μm 2 ≤S2≤0.0100μm 2 , optionally, 0.0008 μm 2 ≤S2≤0.0080μm 2 .
11. The isolation film according to any one of claims 1 to 10, wherein: The average pore size of the isolation membrane is denoted as d1, and the average pore size of the porous substrate is denoted as d2, then d1 / d2<1; Optionally, 0.3≤d1 / d2≤0.8; Optionally, 15nm≤d1≤50nm, more preferably, 20nm≤d2≤40nm; Optionally, 25nm≤d2≤60nm, more optionally, 30nm≤d2≤50nm.
12. The isolation film according to any one of claims 1 to 11, wherein: The surface density of the coating is denoted as ρ1, and the surface density of the porous substrate is denoted as ρ2, then 0.15≤ρ1 / ρ2≤0.80; Optionally, 0.20≤ρ1 / ρ2≤0.50; Optionally, 0.50 g / m 2 ≤ρ1≤1.50g / m 2 , more preferably, 0.75 g / m 2 ≤ρ1≤1.40g / m 2 ; Optionally, 1.50 g / m 2 ≤ρ2≤4.50g / m 2 , more preferably, 2.00 g / m 2 ≤ρ2≤4.00g / m 2 .
13. The isolation film according to any one of claims 1 to 12, wherein: The porosity of the isolation membrane is recorded as P1, and the porosity of the porous substrate is recorded as P2, then 0.4≤P2 / P1<1; Optionally, 0.55≤P2 / P1≤0.85; Optionally, 20%≤P1≤60%, more preferably, 25%≤P1≤45%; Optionally, 15%≤P2≤45%, more preferably, 20%≤P2≤40%.
14. The isolation film according to any one of claims 1 to 13, wherein: The first filler includes at least one of inorganic particles and organic particles; Optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon oxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate and magnesium fluoride, and more optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, silicon oxide, titanium oxide, zinc oxide, cerium oxide and barium titanate; Optionally, the organic particles include at least one of polystyrene particles, polyacrylic wax particles, melamine formaldehyde resin particles, phenolic resin particles, polyester particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles and polyaryletherketone particles.
15. The isolation film according to any one of claims 1 to 14, wherein: The content of the fibrous material is ≤40 wt %, and can be optionally 5 wt % to 25 wt %, based on the total weight of the coating.
16. The isolation film according to any one of claims 1 to 15, wherein: The morphology of the fiber-like object optionally includes at least one of a rod-like, a tube-like, a rod-like and a fiber-like.
17. The isolation film according to any one of claims 1 to 16, wherein: The average diameter of the fibrous material is ≤40 nm, and can be selected from 10 nm to 35 nm; The average length of the fibrous material is 100 nm to 800 nm, and can be optionally 200 nm to 600 nm; The aspect ratio of the fibrous material is 5 to 60, and can be 10 to 30.
18. The isolation film according to any one of claims 1 to 17, wherein: The fibrous material comprises at least one of an organic material and an inorganic material; Optionally, the organic material comprises at least one of nanocellulose, polytetrafluoroethylene nanofibers and polyamide nanofibers, and optionally, the nanocellulose comprises at least one of cellulose nanofibers, cellulose nanowhiskers and bacterial nanocellulose; Optionally, the inorganic material includes at least one of halloysite nanotubes, nanorod-shaped aluminum oxide, nanorod-shaped boehmite, nanorod-shaped silicon oxide and glass fiber.
19. The isolation film according to any one of claims 1 to 18, wherein: The fibrous material includes nanocellulose; Optionally, the nanocellulose includes hydroxyl groups and anionic modification groups; Optionally, the anion-modified group includes at least one of an amine group, a carboxyl group, a sulfonic acid group, a boric acid group and a phosphoric acid group, and more optionally includes at least one of a sulfonic acid group, a boric acid group and a phosphoric acid group; Optionally, the molar ratio of the anionic modifying group to the hydroxyl group is 1:4 to 4:1, and more preferably 2:3 to 7:
3.
20. The isolation film according to any one of claims 1 to 19, wherein: The coating also includes a non-particulate binder; Optionally, the non-granular binder comprises an aqueous solution binder; Optionally, the content of the non-particulate binder in the coating is ≤ 2 wt %, based on the total weight of the coating.
21. The isolation film according to any one of claims 1 to 20, wherein: The thickness of the porous substrate is ≤8 μm, and can be 3 μm to 6 μm; and / or, The thickness of the coating is ≤2 μm, and can be optionally 0.5 μm to 1.3 μm.
22. The isolation film according to any one of claims 1 to 21, wherein: The isolation film further comprises an adhesive layer, the adhesive layer is disposed on at least a portion of the surface of the coating layer, and the adhesive layer comprises a granular binder; Optionally, the granular binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer.
23. The isolation film according to any one of claims 1 to 22, wherein: The isolation film satisfies at least one of the following conditions (1) to (9): (1) The longitudinal heat shrinkage rate of the isolation film at 150°C for 1 hour is ≤6%, and can be selected from 0.5% to 4%; (2) The transverse heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤6%, and can be selected from 0.5% to 4%; (3) The ion conductivity of the isolation membrane is ≥0.6ms / cm 2 , can be selected as ≥0.9ms / cm 2 ; (4) The resistance value of the isolation film is ≤1.3Ω, and can be ≤1.0Ω; (5) The longitudinal tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 ; (6) The transverse tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 ; (7) The wetted length of the isolation film is ≥30 mm, and can be selected from 30 mm to 80 mm; (8) The wetting speed of the isolation film is ≥3 mm / s, and can be selected from 3 mm / s to 10 mm / s; (9) The air permeability of the isolation membrane is ≤300s / 100mL, and can be optionally 100s / 100mL to 230s / 100mL.
24. A method for preparing the isolation film according to any one of claims 1 to 23, comprising the following steps: A porous substrate is provided; the fibrous material and the filler are mixed in a solvent in a predetermined ratio, and then stirred evenly at a certain shear speed to prepare a coating slurry; the coating slurry is applied on at least one surface of the porous substrate, and an isolation membrane is obtained after drying, wherein the isolation membrane comprises a porous substrate and a coating disposed on at least one surface of the porous substrate, the coating comprising a fibrous material and a filler; the filler comprises a first filler and a second filler, and the average particle size of the second filler is larger than the average particle size of the first filler.
25. The method according to claim 24, wherein: The shearing speed is ≤30 m / s, and can be optionally 15 m / s to 30 m / s; and / or, The solid content of the coating slurry is 8% to 30%, optionally 10% to 20%; and / or, The coating surface density of the coating slurry on one side is 0.50 g / m 2 Up to 1.50g / m 2 , optional 0.75g / m 2 Up to 1.40g / m 2 and / or, The coating thickness of the coating slurry on one side is ≤2 μm, and can be selected to be 0.5 μm to 1.3 μm.
26. The method according to claim 24 or 25, further comprising the steps of: A slurry containing a particulate binder is applied to at least a portion of the surface of the coating layer, and dried to form an adhesive layer. 27 . A secondary battery comprising the separator according to claim 1 or the separator prepared by the method according to claim 24 .
28. An electric device comprising the secondary battery according to claim 27.
Citation Information
Patent Citations
Porous solid membrane used for lithium ion battery and production method thereof
CN101814590A
Nonaqueous-secondary-battery separator and nonaqueous secondary battery
CN104620417A
Ceramic diaphragm and preparation method and application thereof
CN105529425A
Separator, method of preparing the same, and lithium battery including the same
CN110233223A
Cited By
Sodium secondary battery cell and electrical device
WO2026157412A1